Student Worksheets With The Spldv Calc Application To Improve Creative Thinking Abilities - Krisdiana, Ika; Setyansah, Reza Kusuma; Pratiwi, Indah Aditiya (Jurnal Pendidikan Indonesia, 2020)
The purpose of this development research is to develop math worksheets using the SPLDV Calc application and to find out how to improve students' creative thinking skills with a 4D development model that is modified into 3D. The stages of this research development consist of: define, design, and develop. The results of this product development are (1) fulfilling the validity criteria based on the final validation percentage of 87% for LKS and 89% for the SPLDV Calc application; (2) meet the effectiveness criteria based on the results of student learning completeness to achieve classical mastery with a percentage of 86%; (3) meeting the criteria for practicality with a student response questionnaire percentage of 85% giving a positive response. The developed worksheets can improve students' creative thinking skills, it is indicated that there is an increase in the pretest to posttest scores from the N-Gain test score of 0.73 with high interpretation, so that the student worksheets can be used by students in learning This shows that android-based worksheets make it easier to learn mathematics.